Early detection of corrosion activity in reinforced concrete slab by AE technique - Ismail, Mohamed A.; Soleymani, Hamid; Ohtsu, Masayasu (2006)
Chloride induced corrosion of steel reinforcement in concrete is the main cause of damage to concrete structures in marine, or structures exposed to de-icing salt environments. The need for early detection of corrosion in reinforced concrete structures is widely acknowledged in corrosion health monitoring for strategic civil engineering projects. This paper summarizes results from a laboratory experiment, using Acoustic Emission (AE) technique, regarding early detection of corrosion in reinforced concrete slabs that are exposed to chloride. The Results showed that while AE was able to determine the initiation of corrosion in reinforced concrete slab, Half-cell potential (HCP) was not able to detect it at the early stage of corrosion.